The Influence of Transformational Leadership Style, Motivation and Work Discipline on Aviation Security Officers at Hang Nadim Airport Batam, Riau Archipelago - David Humala Sitorus; M.Khoiri; Inda Sukati (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the effect of leadership style, work motivation and work discipline on the performance of aviation security officers at Hang Nadim Airport Batam. The independent variables used in this study are transformational leadership style, work motivation and work discipline. Meanwhile, the dependent variable in this study is employee performance. This study used a sample of 105 respondents who were taken using the non-probability sample method. The data analysis technique used is descriptive analysis, reliability test, classic assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear analysis test, analysis of the coefficient of determination hypothesis test t test and f test using the SPSS 25 application. Analysis on research this results that transformational leadership style has a significant influence on employee performance, work motivation has a significant influence on employee performance and work discipline has a significant influence on employee performance and simultaneously all variables have a positive and significant effect